2020
DOI: 10.1186/s13000-020-01025-8
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent uterine tumors resembling ovarian sex-cord tumors with the growth regulation by estrogen in breast cancer 1-nuclear receptor coactivator 2 fusion gene: a case report and literature review

Abstract: Background Uterine tumors resembling ovarian sex-cord tumors (UTROSCTs) are rare mesenchymal neoplasms predominantly arising in perimenopausal and postmenopausal women. UTROSCTs with growth regulation by estrogen in breast cancer 1 (GREB1)-rearrangement or GREB1-rearranged uterine tumors are exceptionally rare, with only 12 previously reported cases. Here, we report a case of UTROSCT with the GREB1-nuclear receptor coactivator 2 (NCOA2) fusion gene. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 24 publications
(40 reference statements)
0
55
0
Order By: Relevance
“…The NCOA1-3 genes encode nuclear receptor co-activators 1 to 3, belonging to the p160 family of steroid receptor co-activators, that when bound to nuclear receptors, stimulate transcription in a hormone-dependent manner. As uterine tissues typically show high ESR1 and GREB1 expression, the putative fusion oncoproteins retain the active promoter region of ESR1/GREB1 fused to the nuclear receptor coactivator domain of NCOA1-3, resulting in dysregulated expression of NCOA1-3, thus enhancing or interfering with the transactivation functionality (4,(10)(11)(12)(13). For GERB1-NCOA fused UTROSCTs, the breakpoints in GREB1 are reported to be located at exon 2 to intron 8, and in NCOA genes the breakpoints are usually located at exon 13 to 15 (3).…”
Section: Uterine Tumor Resembling Ovarian Sex Cord Tumormentioning
confidence: 99%
See 1 more Smart Citation
“…The NCOA1-3 genes encode nuclear receptor co-activators 1 to 3, belonging to the p160 family of steroid receptor co-activators, that when bound to nuclear receptors, stimulate transcription in a hormone-dependent manner. As uterine tissues typically show high ESR1 and GREB1 expression, the putative fusion oncoproteins retain the active promoter region of ESR1/GREB1 fused to the nuclear receptor coactivator domain of NCOA1-3, resulting in dysregulated expression of NCOA1-3, thus enhancing or interfering with the transactivation functionality (4,(10)(11)(12)(13). For GERB1-NCOA fused UTROSCTs, the breakpoints in GREB1 are reported to be located at exon 2 to intron 8, and in NCOA genes the breakpoints are usually located at exon 13 to 15 (3).…”
Section: Uterine Tumor Resembling Ovarian Sex Cord Tumormentioning
confidence: 99%
“…While the identification of similar molecular abnormalities in the majority of cases provides strong support that UTROSCT is a distinct entity, there is significant clinicopathologic heterogeneity within this disease spectrum (1). Genotype and phenotype correlation has suggested that GREB1-rearranged UTROSCTs may have a higher tendency to behave aggressively (3,(10)(11)(12)(13). Herein, we report a UTROSCT with aggressive histologic features harboring a GREB1-NCOA2 fusion detected by RNA sequencing and validated by fluorescence in situ hybridization (FISH) analysis, with an emphasis on the diagnostic implications.…”
mentioning
confidence: 93%
“…The data for 23 UTROSCTs were collected from 2014 to 2021, including 4 diagnosed and treated with surgery at Fudan University Shanghai Cancer Center and 19 consultation patients with available slides and tissues. One of the cases was previously reported 15 . Another case was consulted in our department and reported by a local gynecologist, who sent the case for consultation 16 .…”
Section: Methodsmentioning
confidence: 99%
“…Those more aggressive subtypes have been associated with extensive rhabdoid differentiation and GREB1 and ESR1-NCOA2 fusions. 114 117 …”
Section: Other Infrequent Subtypes: Adenosarcoma Pecoma Uterine Tumor...mentioning
confidence: 99%